Pengembangan Sistem Manajemen Peminjaman Sarana dan Prasarana (Studi Kasus : Fakultas Hukum Universitas Brawijaya) - Sueddi Sihotang; Achmad Arwan; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Faculty of Law Universitas Brawijaya conducts lecture activities every day but does not have the media to submit lecture information online. The Faculty of Law, Universitas Brawijaya also has activities outside of lectures that use space and supporting equipment so that the activity can run well. The needs of students in using faculty rooms and equipment have been met so far. Students can borrow rooms and goods to the faculty which have been done manually. Every loan must be validated by the head of the academic, the head of the student body and the head of the general. This validation process sometimes takes a long time if these people cannot be found within a certain time. The loan facility and infrastructure management system is a system that can overcome the above problems. Submitting a loan and validating a loan can be done online. Every loan will be recapitulated by the system. The system was developed by the waterfall method and uses an object oriented approach. Developers use codeigniter as a framework for implementing systems because it supports the concept of MVC (model, view, controller). System testing is done by using black-box testing and white-box testing to test the functional system and using compatibility testing to test non-functional systems. Based on the tests conducted, the system gets 100% valid functional test results and gets good results in compatibility testing because it is able to run well in the browser environment under test.